Anomalies in the 110 VDC System at PT. PLN (Persero) Transmission Service Unit and Binjai Substation - Gunoro; Juli Iriani; Dian Anggina Thamrin; Cholish; Abdullah (CERED Indonesia Institute, 2022)
Anomalies in the DC system, both in the rectifier and the battery, will occur sooner or later, and the cause is equipment age, maintenance, and fault. The purpose of this study was to determine the anomaly that occurred in the 110 VDC system at PT. PLN ULTG Binjai. The research method is to observe, examine and measure the DC system. The research was carried out at the Paya Geli Substation and Pangkalan Brandan Substation. From the results of the study, it was found that the anomaly that occurred in the 110 VDC system at ULTG Binjai was the final voltage per battery cell which was less than 1 volt, namely the battery cell numbers 1, 34 and 39 in the Payageli substation 2 bank battery. DC ground occurs in bank 1 at the Paya Geli substation with the negative side connected to ground, the positive side voltage to ground is 95.2 volts, while the voltage on the negative side to ground is 8.4 volts. The main fault (phase loss) anomaly at the Pangkalan Brandan substation was due to the burning of the input line in the rectifier control module, causing the rectifier to fail and the DC supply from the rectifier to be lost and temporarily supplied by the battery. Regular maintenance is required for reliability to avoid anomalies and immediately recondition if the battery capacity is less than 60% and the final voltage per battery cell is less than 1 volt.